Developmental changes in estrogen-sensitive neurons in the forebrain of the zebra finch. - Gahr, M (1988)
The brain areas for the control of song are sexually dimorphic in the zebra finch (Poephila guttata). Implantation of estrogen in young females within the first 40 days after hatching masculinizes their brain song areas. Monoclonal antibody (H222Sp gamma) against the estrogen receptor was used for the localization of estrogen-target cells in the brain. The nucleus hyperstriatum ventrale, pars caudale, was the only song control area that contained cells with estrogen-receptor sites. The number of these cells varied during ontogeny and declined sharply after day 40. No other song areas contained estrogen-target cells despite their ability to undergo masculine differentiation under the influence of estrogen. Therefore, the action of estrogen on these nuclei must be indirect.